2000
DOI: 10.1111/j.1532-5415.2000.tb04754.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on the Relationship Between Multiple Risk Factors and Waist Circumference

Abstract: Our data indicate that the waist circumference cutpoints proposed by NHLBI and WHO standards are useful for the prediction of cardiovascular disease risk factors in older as well as in younger men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
0
28
0
2
Order By: Relevance
“…40 Iwao et al 91 reported significant associations between waist and coronary risk factor abnormalities. 91 They found a significant correlation among BMI, waist circumference and the risk factors (blood pressure, glucose levels, dyslipidaemia) in young as well as in older people. 91 In the Iowa Women Health Study, a sample of over 30 000 women with age ranging from 55 to 69 y and a mean followup of 10 y, both BMI and waist-to-hip ratio, were significant predictors of incident diabetes and hypertension.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 96%
See 1 more Smart Citation
“…40 Iwao et al 91 reported significant associations between waist and coronary risk factor abnormalities. 91 They found a significant correlation among BMI, waist circumference and the risk factors (blood pressure, glucose levels, dyslipidaemia) in young as well as in older people. 91 In the Iowa Women Health Study, a sample of over 30 000 women with age ranging from 55 to 69 y and a mean followup of 10 y, both BMI and waist-to-hip ratio, were significant predictors of incident diabetes and hypertension.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 96%
“…91 They found a significant correlation among BMI, waist circumference and the risk factors (blood pressure, glucose levels, dyslipidaemia) in young as well as in older people. 91 In the Iowa Women Health Study, a sample of over 30 000 women with age ranging from 55 to 69 y and a mean followup of 10 y, both BMI and waist-to-hip ratio, were significant predictors of incident diabetes and hypertension. 55 In addition, in younger as well as older subjects, obesity and fat distribution indices are linked not just to individual metabolic abnormalities but also to the co-occurrence of metabolic alterations, the so-called Metabolic Syndrome.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 96%
“…[28][29][30][31][32] In the present study, there was an interesting finding that correlations between BMI, WC and lipids (total and LDLcholesterol) in older people were weak or not significant regardless of populations, although BMI and WC were still highly correlated with triglycerides and HDL-cholesterol in older people. We have previously reported the effects of age on the relationship between body composition and risk factors in Caucasians 15,16,33 and these effects are also seen in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports on a Caucasian population 15,16 showed that BMI and WC independently were significant predictors of coronary risk factors in the blood pressure, glucose- Racial differences in risk factors and fat distribution N Iwao et al insulin and plasma lipid domains. Furthermore, the gradation of BMI into normal, overweight and obese zones according to NHLBI 5 and WHO 6 recommendations was supported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation